Effect of the teaching model on the individual technique of soccer players sub-10 - Pérez-Muñoz, S.; Chamorro-Juanes, P.; Rodríguez-Cayetano, A.; Sánchez-Muñoz, A.; De Mena-Ramos, JM. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The aim of the study was to compare the effect of the teaching model on the improvement of individual technique in both legs of soccer players sub-10. We analyzed 12 players who made eight sessions with a traditional model and eight with an innovative model. It was measured: pass, control, driving and hitting the ball. The traditional model improves the pass and hit with the right and the ball driving with both feet, with significant differences (p <.05) in the right pass and the ball driving with both legs. In the innovative model improves the pass with dominant foot, linear driving with both feet and hitting the ball on goal with both feet, with significant differences in the driving of the ball with both legs (p <.05). For these reasons, the improvement of the individual technique of the players requires the use of traditional and innovative models.